Direct conversion of syngas to gasoline ranged olefins over Na impellent Fe@NaZSM-5 catalyst. (15th January 2022) - Li, Mingquan; Noreen, Aqsa; Fu, Yajie; Amoo, Cederick Cyril; Jiang, Yujia; Sun, Xu; Lu, Peng; Yang, Ruiqin; Xing, Chuang; Wang, Shurong
Highlights: One-step conversion of CO to higher olefins (C5+ ) over Fe@NaZSM-5 catalyst. Na-Zeolite offers Na electron promoter. Na ions enhanced the formation of Fe5 C2 phases which favors olefins selectivity. Abstract: Directly synthesizing olefins from syngas using metal-zeolite composite catalysts has engrossed a lot of attention recently. Fe-based catalysts will be the most promising industrial candidates due to cost and availability constraints. In this work, we investigate the characteristics and Fischer-Tropsch activity of a novel Fe@Na-ZSM-5 composite for one-step conversion of syngas to higher olefins (C5+ ). The in-situ crystallization mechanism induced Na in the ZSM-5 as a Fe-based promoter which realized 52.5 % selectivity for gasoline of which ∼ 70% were olefins. Additionally, the promotion by the Na ions enhanced the formation of Fe5 C2 phases which in turn favored C–C coupling, high gasoline and olefins selectivity. Na type zeolite (Na-Zeolite) offers a novel Na electron promoter, which participate immensely in the development of heterogenous catalyst and functional materials.